EFFECT OF METFORMIN ON HEART RATE VARIABILITY IN NEWLY DIAGNOSED TYPE 2 DIABETES MELLITUS PATIENTS AT A TERTIARY CARE HOSPITAL - RATHOD, KHUSHBU; YADAV, PREETI; CHAUDHARI, MAYUR; VASAVA, ASHVIN; PATEL, MRUGANK (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: There is a worldwide epidemic of type 2 diabetes mellitus (T2DM). It is associated with cardiovascular autonomic neuropathy. Heart rate variability (HRV) is the gold standard for its measurement. Thus, effect of metformin therapy on HRV was evaluated in newly diagnosed T2DM patients. Methods: This was a prospective and observational study carried out from January 2020 to September 2021 in the medicine outpatient department of a tertiary care hospital in Gujarat, India. The study included newly diagnosed T2DM patients of both genders aged 18–70 years. Baseline HRV parameters were recorded by performing electrocardiogram for a fixed duration of 5 min. Follow-up was done after 6 months of metformin 500 mg monotherapy. Time domain analysis was done using square root of mean square of successive R-R interval difference (RMSSD) and frequency domain analysis was done using low-frequency/high-frequency (LF/HF) ratio. Paired t-test was used for analysis. p<0.05 was considered statistically significant. Results: Total 30 patients were included in the study. The average age of participants was 43.5±4.5 years. The highest number of patients were from age group between 41 and 50 years (33.3%). There were more number of females (56.7%) compared to males (43.3%). There was an increase in the RMSSD value after metformin treatment, but it was not statistically significant (p=0.308). In frequency domain analysis, there was no significant improvement in LF, HF, as well as LF/HF ratio (p=0.655). Conclusion: There was a minor improvement in HRV parameters after 6 months of metformin therapy, but it was not statistically significant. Further studies with larger sample size should be planned with one or more oral hypoglycemics.